Strengthening channeling policy: the Finnish approach to protecting domestic online gambling market - Järvinen-Tassopoulos, Johanna; Marionneau, Virve; Egerer, Michael (Frontiers in Sociology, 2024)
Many jurisdictions struggle to curb offshore gambling as established approaches to gambling regulation no longer apply to online gambling. This study aimed to examine the arguments used by Finnish stakeholders who discussed channeling as a tool to curb offshore gambling and the monopolistic gambling regime as a sustainable framework to tackle the issue of offshore gambling. In total, 18 Finnish public servants employed in ministries in charge of gambling matters and representatives of Veikkaus, the state-owned gambling company, were interviewed for the purpose of this study. Channeling was described by the interviewees as an important policy tool but without a regulatory framework to block offshore operation, it would remain an ideal type of political strategy. Beside the monopolistic gambling regime, the pros and cons of a potential licensing regime were discussed. This study showed that legislative and regulatory changes form a lengthy political process; the decrease of the market share of online gambling marked the beginning of a new era in Finland’s gambling policy.